Jigsaw Strategy in Teaching Reading for Senior High School Students - Machfudi, Moch. Imam; Fajria, Salsabila Umi Nur (Journal of Language Intelligence and Culture, 2023)
This study examines the teaching of reading which considered a crucial component of ELT. This is seen as one method of obtaining information and expanding language proficiency. But according to new, up-to-date research on language instruction, teachers actually give boring lessons. This research employed qualitative research with phenomenology design which intended to investigate how the teacher plan and implement a jigsaw strategy in teaching reading for the students of Islamic High School; hence called Madrasah Aliyah (MA) Miftahul Ulum Suren Jember – East Java and to explore how the teacher reflects their strategy in teaching reading. This research reveals that: the teacher prepared their teaching reading by providing lesson plan that refers to the English syllabus. In the implementation phase, the teacher elaborated the plan by organising it in three main activity including pre-activity, whilst or core activity and final activity. The teacher reflected that teaching reading using jigsaw strategy found to be effective to improve students’ performances.